Perlindungan Hukum terhadap Anak Sebagai Korban Kekerasan Seksual Berbasis Elektronik Berdasarkan Hukum Positif Indonesia - Lombogia, Gratia Prilia; Lasut, Meiske M. W.; Lolong, Wenly R.J. (Wajah Hukum, 2026)
Cases of electronic-based sexual violence (KSBE) are increasing in the digital age, resulting in serious psychological and social impacts, especially for children as victims. This study aims to understand the legal protection for child victims of KSBE based on Indonesian positive law and to understand how the law responds to such crimes. The research method used is normative research with a legislative and conceptual approach. The results show that Indonesian positive law has a significant legal protection framework for child victims of ESV, including the Child Protection Law, the Sexual Violence Criminal Law, and other related regulations. The legal protection provided covers various aspects, including health services and psychosocial assistance, the right to protection in the judicial process, the right to restitution, and the right to the removal of sexual content. The penalties include imprisonment and fines with various ranges, adjusted to the level of violation, in accordance with relevant legal regulations. However, even though this legal framework is in place, its implementation still faces challenges, such as a lack of understanding among law enforcement officials and incomplete implementing regulations. Therefore, this study also provides policy recommendations to strengthen legal protection for child victims of KSBE.